Perlindungan Hukum Terhadap Konsumen Yang Dirugikan Atas Perbuatan Kartel Produsen Kendaraan Bermotor - Chelsea Angelia Hartono; Lanny Kusumawati; Irta Windra Syahrial (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
This thesis raises a case regarding the actions and implementation of a cartel agreement between the President Director of PT X and the President Director of PT Y with the object of a 110 cc & 125 CC automatic scooter that does not meet the statutory provisions, namely article 1320 number (4), 1338 paragraph (3) and 1365 of the Criminal Code in conjunction with Article 5 paragraph (1), Article 11, and 47 of Law No. 5 of 1999 in conjunction with Article 4 and Article 45 paragraph (1) of Law No. 8 of 1999, which resulted in unlawful acts. The non-compliance with the statutory provisions was because the automatic scooter motorcycle was motivated by the existence of a cartel agreement between the President Director of PT X and the President Director of PT Y in violation of Article 5 paragraph (1). So that the price fixing agreement made has violated the legal requirements of an agreement, namely "a lawful cause" where as a result the agreement is null and void. For their actions, the two PTs violating the provisions of the law can be said to be an unlawful act in accordance with Article 1365 of the Criminal Code, in which all elements of unlawful acts have been fulfilled. Based on Article 1365 of the Criminal Code, then PT X and PT Y as business actors producing motorized vehicles obliged to be responsible for an act against the law that brings harm to the consumers as buyers. Keyword: Cartel Agreement; Pricing Agreement; Tort; Liability